A Comparative Study of Pollution Levels in Major Cities of India During Covid-19 in India - Manohar Kapse; Bakki Akhil; N. Elangovan; Vinod Sharma; K. Rajagopal (Australasian Accounting, Business and Finance Journal, 2023)
This paper aims to study the major pollutants of the four metro cities of India before and after covid 19 first wave. The cities considered for the study are Bangalore, Delhi, Mumbai, and Kolkata. The major pollutants considered for the study are PM2.5, PM10, NO, NO2, NOx, SO2, CO, and Ozone. The basic aim of the study is to find the effect of lockdown and covid restrictions on the level of pollutants across the four major cities of India. We used both parametric and non-parametric tests for the analysis using SPSS. From the study, it is clear that there is a significant decrease in all the major pollutants across India's major cities.
Keywords: Covid-19; pollutants; PM2.5; PM10; NO; NO2; NOx; SO2; CO; Ozone